Aluminum-plastic film with high thermal conductivity and high deep-drawing performance, preparation method of aluminum-plastic film and lithium ion battery
By adopting composite layer structure and high thermal conductivity BN inorganic particles in aluminum-plastic films, combined with hot pressing bonding and corona treatment technology, the problem of difficult to take into account both the thermal conductivity and the depth performance of aluminum-plastic films is solved, and efficient heat dissipation and excellent depth performance are achieved to ensure the safety of lithium-ion batteries.
Patent Information
- Application Number
- CN202411615527.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing aluminum-plastic films are difficult to take into account both thermal conductivity and depth performance, resulting in fires that may be caused during high-temperature charging and discharging.
The aluminum-plastic film structure is adopted in which the composite nylon film layer, adhesive layer, aluminum foil layer and CPP film layer are laminated in sequence from outside to inside. The adhesive layer is made of AB two-component polyurethane glue, and the CPP film layer contains BN inorganic particles, and its performance is enhanced by hot pressing bonding and corona treatment.
The high thermal conductivity and excellent depth performance of aluminum-plastic film are achieved, so that lithium-ion batteries can effectively dissipate heat under high temperature conditions and evenly disperse stress during pit flushing, avoiding fires.
Smart Images

Figure CN119502510A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum-plastic films for lithium batteries, and in particular relates to an aluminum-plastic film with high thermal conductivity and high punching performance, a preparation method thereof, and a lithium-ion battery. Background Art
[0002] With the rapid development of the soft-package lithium-ion battery application industry, higher performance requirements have been put forward for aluminum-plastic films. Lithium batteries release heat during the charging and discharging process. In addition, most electric vehicles are charged under the scorching sun in summer. When the battery is charged and discharged at high temperatures, the positive and negative electrodes will react with the electrolyte and release additional heat. If a large amount of heat cannot be dissipated in time, it is very easy to cause the diaphragm to melt, and it will get out of control and cause a fire. This puts forward high thermal conductivity requirements for soft-package lithium batteries.
[0003] In order to overcome the defect of insufficient thermal conductivity, existing aluminum-plastic films often add high thermal conductivity materials to assist in heat dissipation, but this brings about a new defect of insufficient deep drawing performance.
[0004] Therefore, how to solve the problem that the thermal conductivity and deep drawing performance of aluminum-plastic film cannot be taken into account at the same time is a technical problem that needs to be solved urgently in this field.
[0005] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention
[0006] The embodiments of the present disclosure at least provide an aluminum-plastic film with high thermal conductivity and high punching performance, a preparation method thereof, and a lithium-ion battery.
[0007] In the first aspect, the embodiments of the present disclosure provide an aluminum-plastic film with high thermal conductivity and high drawing performance, comprising: a nylon film layer, an adhesive layer, an aluminum foil layer and a CPP film layer laminated in sequence from the outside to the inside; wherein the adhesive layer is made of AB two-component polyurethane glue; the A component comprises the following components in parts by mass: 20-35 parts of polyester polyol, 15-25 parts of polyether polyol, 5-10 parts of polyisocyanate monomer, 1-5 parts of silane coupling agent, 1-5 parts of graphene oxide and 40-60 parts of solvent; the B component comprises the following components in parts by mass: 95-99 parts of polyisocyanate curing agent and 1-5 parts of solvent; the CPP film layer is a corona layer, a support layer and a heat sealing layer from the aluminum foil layer to the outside, and all contain BN inorganic particles.
[0008] In an optional embodiment, the corona layer comprises the following components in parts by mass, and the total parts are 100 parts: 50-60 parts of MPP resin, 30-40 parts of homopolypropylene resin, 1-5 parts of lubricating masterbatch and 1-5 parts of BN inorganic particles.
[0009] In an optional embodiment, the support layer comprises the following components in parts by mass, and the total parts are 100 parts: 85-95 parts of homopolymer polypropylene resin, 1-5 parts of lubricating masterbatch and 1-5 parts of BN inorganic particles.
[0010] In an optional embodiment, the heat-sealing layer comprises the following components in parts by mass, and the total parts are 100 parts: 80-90 parts of ternary copolymer polypropylene resin, 2-8 parts of hyperbranched amide resin, 1-5 parts of slip masterbatch and 1-5 parts of BN inorganic particles.
[0011] In an optional embodiment, the mass fraction ratio of the A component to the B component is 100:
[0012] (20-32).
[0013] In an optional embodiment, the thickness range of the nylon film layer is 15-25 μm; the thickness range of the adhesive layer is 3-5 μm; the thickness range of the aluminum foil layer is 35-55 μm; the thickness range of the CPP film layer is 40-60 μm; wherein the thickness ratio of the corona layer, the support layer and the heat sealing layer in the CPP film layer is 1:2:2.
[0014] In an optional embodiment, the particle size of the BN inorganic particles is 100-150 um.
[0015] In an optional embodiment, the graphene oxide has a flake thickness of 80-120 nm.
[0016] In the second aspect, the embodiment of the present disclosure also provides a method for preparing an aluminum-plastic film with high thermal conductivity and high drawing performance as described above, comprising the following steps: step S1, mixing various raw materials in proportion and then performing clean metering feeding; step S2, program temperature control, setting the temperature of the melt extruder, filter and transmission pipeline to 220-240°C, the temperature of the distributor and the T-die to 240°C, to obtain a filtered melt; step S3, passing the filtered melt through the T-die and then non-mirror casting, and then After cooling and crystallization, the film is formed, wherein the casting speed is 40-60 m / min to obtain a pre-prepared CPP film layer; step S4, measuring the pre-prepared CPP film layer and adjusting the thickness, the surface is treated with ozone corona to form a corona layer, and the film is drawn and rolled to obtain a CPP film layer; step S5, coating both sides of the aluminum foil with an acid-resistant agent to form an acid-resistant film to obtain an aluminum foil layer; step S6, hot pressing the bright surface of the treated aluminum foil layer and the CPP film corona layer, and the pressure is 0.3-0.5 MPa, the pressing temperature is 160-180°C, the oven temperature is 200-220°C, and the speed is 30-40m / min to obtain a semi-finished aluminum foil layer; step S7, adding polyester polyol and polyether polyol to the reaction kettle, heating to 120°C-130°C, stirring under vacuum for 2-3h, cooling to 40°C, and sequentially adding polyisocyanate monomer, silane coupling agent, graphene oxide and solvent to the reaction kettle, heating to 90-110°C, stirring under vacuum for 3-6h, to obtain Component A; adding component B consisting of a polyisocyanate curing agent and a solvent to component A, and vacuum stirring for 1 hour to obtain polyurethane glue; step S8, coating and laminating the matte surface of the semi-finished aluminum foil layer in step S6 and the nylon film with the polyurethane glue in step S7, with the glue thickness of 3-5um, the pressure of 0.3-0.5MPa, the laminating temperature of 60-70°C, the oven temperature of 70-90°C, and the speed of 60-80m / min to obtain an aluminum-plastic film with high thermal conductivity and high drawing performance.
[0017] In a third aspect, the embodiments of the present disclosure further provide a lithium-ion battery, comprising the aluminum-plastic film with high thermal conductivity and high punch depth performance as described above.
[0018] The beneficial effects of the present invention are that the aluminum-plastic film with high thermal conductivity and high punching depth performance and its preparation method, and the lithium-ion battery add high thermal conductivity material boron nitride inorganic particles to the CPP film material to change the crystallization nucleation rate of the CPP film, thereby enhancing the thermal conductivity of the CPP film so that heat can be quickly conducted to the outside of the battery, and improving the molecular arrangement in the CPP film to an orderly arrangement, and cooperating with the ductility and thermal conductivity of graphene oxide in the adhesive layer, so that the overall thermal conductivity of the aluminum-plastic film is improved and the stress can be evenly dispersed during punching, thereby obtaining excellent punching depth performance.
[0019] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description, claims and drawings.
[0020] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 A schematic structural diagram of an aluminum-plastic film with high thermal conductivity and high drawing performance provided in an embodiment of the present disclosure.
[0023] In the figure:
[0024] 1. Nylon film layer; 2. Adhesive layer; 3. Aluminum foil layer; 41. Corona layer; 42. Support layer; 43. Heat sealing layer. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.
[0027] Herein, example embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as "at least one of..." modify the entire list of elements when following a list of elements, rather than modifying individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.
[0028] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.
[0029] Aluminum-plastic film is the main packaging material for soft-pack lithium batteries. It is mainly composed of a four-layer structure, which is composed of a nylon film layer, an adhesive layer, an aluminum foil layer and a CPP film layer from the outside to the inside. The CPP film is in direct contact with the electrolyte and is the key to heat dissipation. At the same time, the adhesive layer also plays an important role in the heat conduction process.
[0030] Specifically, CPP film refers to cast polypropylene film, MPP resin refers to a polymer obtained by polymerizing propylene or copolymerizing propylene mainly with one or more other unsaturated compounds, and BN inorganic particles refer to boron nitride inorganic particles.
[0031] Therefore, in the existing process, only improving the CPP film layer cannot completely solve the thermal conductivity problem of the aluminum-plastic film.
[0032] The defects existing in the above solutions are the results obtained by the inventor after practice and careful research. Therefore, the discovery process of the above problems and the solutions proposed by the present disclosure for the above problems below should be the contributions made by the inventor to the present disclosure during the disclosure process.
[0033] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0034] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0035] See also Figure 1 ,like Figure 1 As shown, the embodiment of the present disclosure provides an aluminum-plastic film with high thermal conductivity and high drawing performance, comprising: a nylon film layer, an adhesive layer, an aluminum foil layer and a CPP film layer laminated in sequence from the outside to the inside; wherein the adhesive layer is made of AB two-component polyurethane glue; the A component comprises the following components in parts by mass: 20-35 parts of polyester polyol, 15-25 parts of polyether polyol, 5-10 parts of polyisocyanate monomer, 1-5 parts of silane coupling agent, 1-5 parts of graphene oxide and 40-60 parts of solvent; the B component comprises the following components in parts by mass: 95-99 parts of polyisocyanate curing agent and 1-5 parts of solvent; the CPP film layer is a corona layer, a support layer and a heat sealing layer from the aluminum foil layer to the outside, and all contain BN inorganic particles.
[0036] In some embodiments, specifically, the corona layer includes the following components in mass fractions, and the total mass fractions are 100: 50-60 parts of MPP resin, 30-40 parts of homopolymer polypropylene resin, 1-5 parts of lubricating masterbatch, and 1-5 parts of BN inorganic particles. The corona layer can firmly adhere to the bright surface of the aluminum foil through corona, greatly improving the electrolyte resistance, so that the corrosion resistance of the CPP film is greatly enhanced.
[0037] In some embodiments, specifically, the support layer includes the following components in mass fractions, and the total mass fractions are 100: 85-95 parts of homopolymer polypropylene resin, 1-5 parts of lubricating masterbatch, and 1-5 parts of BN inorganic particles. The support layer is in the middle of the CPP film, and plays a connecting role. It is mainly used to support the stable morphological structure of the CPP film, which is not easy to deform, so that the corona layer and the heat sealing layer do not interfere with each other.
[0038] In some embodiments, specifically, the heat-sealing layer includes the following components in parts by mass, and the total parts are 100 parts: 80-90 parts of terpolymer polypropylene resin, 2-8 parts of hyperbranched amide resin, 1-5 parts of lubricating masterbatch, and 1-5 parts of BN inorganic particles. The heat-sealing layer determines the heat-sealing strength of the aluminum-plastic film as a whole, and its strength directly determines whether there will be electrolyte leakage after the aluminum-plastic film is heat-sealed.
[0039] In some embodiments, specifically, the mass fraction ratio of the A component to the B component is 100:
[0040] (20-32).
[0041] In some embodiments, specifically, the thickness of the nylon film layer is in the range of 15-25 μm; the thickness of the adhesive layer is in the range of 3-5 μm; the thickness of the aluminum foil layer is in the range of 35-55 μm; the thickness of the CPP film layer is in the range of 40-60 μm; wherein the thickness ratio of the corona layer, the support layer and the heat sealing layer in the CPP film layer is 1:2:2.
[0042] In some embodiments, specifically, the particle size of the BN inorganic particles is 100-150 μm, preferably 120 um.
[0043] In some embodiments, specifically, the flake thickness of the graphene oxide is 80-120 nm, preferably 100 nm.
[0044] The embodiment of the present disclosure also provides a method for preparing an aluminum-plastic film with high thermal conductivity and high drawing performance as described above, comprising the following steps: step S1, mixing various raw materials in proportion and then performing clean metering feeding; step S2, program temperature control, setting the temperature of the melt extruder, the filter and the transmission pipeline to 220-240°C, the temperature of the distributor and the T-die to 240°C, to obtain a filtered melt; step S3, passing the filtered melt through the T-die and then performing non-mirror casting, and then cooling the melt; crystallization, shaping and film formation, wherein the casting speed is 40-60m / min, and a pre-prepared CPP film layer is obtained; step S4, measuring and adjusting the thickness of the pre-prepared CPP film layer, treating the surface with ozone corona to form a corona layer, and winding the film to obtain a CPP film layer; step S5, coating both sides of the aluminum foil with an acid-resistant agent to form an acid-resistant film to obtain an aluminum foil layer; step S6, hot-pressing the bright surface of the treated aluminum foil layer and the CPP film corona layer at a pressure of 0.3-0.5MPa , the pressing temperature is 160-180°C, the oven temperature is 200-220°C, the speed is 30-40m / min, and a semi-finished aluminum foil layer is obtained; step S7, polyester polyol and polyether polyol are added to the reaction kettle, the temperature is raised to 120°C-130°C, and the reaction is stirred under vacuum for 2-3h, and the temperature is lowered to 40°C, and polyisocyanate monomer, silane coupling agent, graphene oxide and solvent are added to the reaction kettle in sequence, the temperature is raised to 90-110°C, and the reaction is stirred under vacuum for 3-6h to obtain components A; adding component B composed of a polyisocyanate curing agent and a solvent to component A, and stirring in vacuum for 1 hour to obtain polyurethane glue; step S8, coating and bonding the matte surface of the semi-finished aluminum foil layer in step S6 and the nylon film with the polyurethane glue in step S7, with a glue thickness of 3-5um, a pressure of 0.3-0.5MPa, a bonding temperature of 60-70°C, an oven temperature of 70-90°C, and a speed of 60-80m / min to obtain an aluminum-plastic film with high thermal conductivity and high drawing performance.
[0045] Specifically, in step S6, the MPP resin is hot-pressed and firmly bonded to the aluminum foil to resist corrosion from the electrolyte.
[0046] The disclosed embodiment also provides a lithium-ion battery, comprising the aluminum-plastic film with high thermal conductivity and high punch depth performance as described above.
[0047] The performance of the aluminum-plastic film provided by the present invention is tested according to the following method:
[0048] (1) Heat seal strength
[0049] Using the Japanese Tester Sangyo TP-701-B heat sealer, two 10cm*10cm aluminum-plastic films were heat-sealed at the heat-sealing layer under the conditions of heat-sealing temperature of 190℃, pressure of 0.5MPa, and heat-sealing time of 3s. After the sample cooled to room temperature, the heat-sealing strength was tested using the Shimadzu AGS-X series electronic universal testing machine.
[0050] (2) Deep pit
[0051] Punch holes with a shell punching machine. Start punching from 5.0mm, punch 10 samples continuously, check under strong light for no delamination, cracks, or pinholes, then increase by 0.3mm and continue punching for 10 more until it breaks. Record the punching depth before breakage as the limit punching depth.
[0052] (3) Determination of thermal conductivity of aluminum-plastic film
[0053] First, use the ZMD-1 density balance to test the density of the prepared composite material in accordance with the method of GB / T6343-95; then use the differential scanning calorimeter to compare the measurement results of the standard sample (aluminum oxide) with known specific heat and the sample with unknown specific heat to calculate the specific heat value of the unknown sample; finally, use the laser thermal conductivity meter (Germany Netzsch LFA447) to measure the thermal diffusion coefficient of the sample in accordance with the ASTME1461 standard. Then calculate the thermal conductivity of the sample based on the measured sample density and specific heat.
[0054] Example 1
[0055] This embodiment provides an aluminum-plastic film with high thermal conductivity and high drawing performance and a preparation method thereof.
[0056] The aluminum foil with a thickness of 45um is coated on both sides with the passivation liquid to form an acid-resistant film, dried in an oven at a temperature of 240-280°C, and then rolled up for use.
[0057] 55 parts of MPP resin, 40 parts of homopolypropylene resin V30G, 4 parts of lubricating masterbatch C8203ZH, and 1 part of BN inorganic particles were uniformly mixed to obtain a corona layer resin.
[0058] 95 parts of homopolymer polypropylene resin V30G, 4 parts of lubricating masterbatch C8203ZH, and 1 part of BN inorganic particles were uniformly mixed to obtain a support layer resin.
[0059] 90 parts of ternary copolymer polypropylene resin TF400, 5 parts of hyperbranched amide resin, 4 parts of slip masterbatch C8203ZH and 1 part of BN inorganic particles were uniformly mixed to obtain a heat sealing layer resin.
[0060] The raw materials after the above-mentioned mixed treatment are put into the metering hopper and mixed in proportion, and then enter the corresponding extruder, filter, transmission pipeline, distributor, and T-die head for pressurized melting and plasticization at a temperature of 240°C, and are extruded through a T-die head for three-layer co-extrusion at a casting speed of 50m / min, and cooled and crystallized to form a film; the thickness of the obtained film is measured, and then the corona power is 30W / (m 2 The surface of the corona layer was subjected to corona treatment under the condition of 1000 rpm and 2000 rpm, and then the film was drawn and rolled up to form a film with a thickness of 50 μm.
[0061] The aluminum foil bright surface after passivation treatment is hot pressed with the CPP film corona layer, with a pressure of 0.4MPa, a pressing temperature of 170℃, an oven temperature of 220℃, and a speed of 30m / min. It is then rolled up for use.
[0062] Add 25 parts of polyester polyol and 15 parts of polyether polyol to the reactor, heat to 120°C-130°C, stir under vacuum for 2-3 hours, cool to 40°C, add 5 parts of polyisocyanate monomer, 4 parts of silane coupling agent, 1 part of graphene oxide and 50 parts of solvent to the reactor in sequence, heat to 90-110°C, stir under vacuum for 3-6 hours to obtain component A; add component B composed of 99 parts of polyisocyanate curing agent and 1 part of solvent to component A, stir under vacuum for 1 hour to obtain polyurethane glue.
[0063] The matte surface of the aluminum foil in the aluminum foil laminating CPP semi-finished product and the nylon film 15um are coated and laminated with the above polyurethane glue, and the glue thickness is 3um. The pressure is 0.4MPa, the laminating temperature is 70℃, the oven temperature is 80℃, and the speed is 60m / min to obtain the final product.
[0064] Example 2
[0065] As provided in Example 1, an aluminum-plastic film with high thermal conductivity and high deep drawing performance and a preparation method thereof.
[0066] The aluminum foil with a thickness of 40um is coated on both sides with the passivation liquid to form an acid-resistant film, dried in an oven at a temperature of 240-280°C, and then rolled up for use.
[0067] 55 parts of MPP resin, 40 parts of homopolypropylene resin V30G, 2 parts of lubricating masterbatch C8203ZH, and 3 parts of BN inorganic particles were uniformly mixed to obtain a corona layer resin.
[0068] 95 parts of homopolymer polypropylene resin V30G, 2 parts of lubricating masterbatch C8203ZH, and 3 parts of BN inorganic particles were uniformly mixed to obtain a support layer resin.
[0069] 90 parts of ternary copolymer polypropylene resin TF400, 5 parts of hyperbranched amide resin, 2 parts of slip masterbatch C8203ZH, and 3 parts of BN inorganic particles were uniformly mixed to obtain a heat sealing layer resin.
[0070] The raw materials after the above-mentioned mixed treatment are put into the metering hopper and mixed in proportion, and then enter the corresponding extruder, filter, transmission pipeline, distributor, and T-die head for pressurized melting and plasticization at a temperature of 240°C, and are extruded through a T-die head for three-layer co-extrusion at a casting speed of 50m / min, and cooled and crystallized to form a film; the thickness of the obtained film is measured, and then the corona power is 30W / (m 2 The surface of the corona layer was subjected to corona treatment under the condition of 1000 rpm and 2000 rpm, and then the film was drawn and rolled up to form a film with a thickness of 55 μm.
[0071] The aluminum foil bright surface after passivation treatment is hot pressed with the CPP film corona layer, with a pressure of 0.4MPa, a pressing temperature of 170℃, an oven temperature of 220℃, and a speed of 30m / min. It is then rolled up for use.
[0072] Add 30 parts of polyester polyol and 19 parts of polyether polyol to the reactor, heat to 120°C-130°C, stir under vacuum for 2-3 hours, cool to 40°C, add 6 parts of polyisocyanate monomer, 3 parts of silane coupling agent, 2 parts of graphene oxide and 40 parts of solvent to the reactor in sequence, heat to 90-110°C, stir under vacuum for 3-6 hours to obtain component A; add component B composed of 98 parts of polyisocyanate curing agent and 2 parts of solvent to component A, stir under vacuum for 1 hour to obtain polyurethane glue.
[0073] The matte surface of the aluminum foil in the aluminum foil laminating CPP semi-finished product and the nylon film 15um are coated and laminated with the above polyurethane glue, and the glue thickness is 3um. The pressure is 0.4MPa, the laminating temperature is 70℃, the oven temperature is 80℃, and the speed is 60m / min to obtain the final product.
[0074] Example 3
[0075] As provided in Example 1, an aluminum-plastic film with high thermal conductivity and high deep drawing performance and a preparation method thereof.
[0076] The aluminum foil with a thickness of 35um is coated on both sides with passivation liquid to form an acid-resistant film, dried in an oven at a temperature of 240-280°C, and then rolled up for use.
[0077] 60 parts of MPP resin, 35 parts of homopolymer polypropylene resin V30G, 2 parts of lubricating masterbatch C8203ZH, and 3 parts of BN inorganic particles were uniformly mixed to obtain a corona layer resin.
[0078] 95 parts of homopolymer polypropylene resin V30G, 2 parts of lubricating masterbatch C8203ZH, and 3 parts of BN inorganic particles were uniformly mixed to obtain a support layer resin.
[0079] 92 parts of ternary copolymer polypropylene resin TF400, 3 parts of hyperbranched amide resin, 2 parts of slip masterbatch C8203ZH, and 3 parts of BN inorganic particles were uniformly mixed to obtain a heat sealing layer resin.
[0080] The raw materials after the above-mentioned mixed treatment are put into the metering hopper and mixed in proportion, and then enter the corresponding extruder, filter, transmission pipeline, distributor, and T-die head for pressurized melting and plasticization at a temperature of 240°C, and are extruded through a T-die head for three-layer co-extrusion at a casting speed of 50m / min, and cooled and crystallized to form a film; the thickness of the obtained film is measured, and then the corona power is 30W / (m 2 The surface of the corona layer was subjected to corona treatment under the condition of 1000 rpm and 2000 rpm, and then the film was drawn and rolled up to form a film with a thickness of 50 μm.
[0081] The passivated aluminum foil bright surface and the CPP film corona layer are hot pressed together at a pressure of 0.4 MPa, a pressing temperature of 170°C, an oven temperature of 220°C, and a speed of 30 m / min. The aluminum foil is then pulled and rolled up for use.
[0082] Add 30 parts of polyester polyol and 19 parts of polyether polyol to the reactor, heat to 120°C-130°C, stir under vacuum for 2-3 hours, cool to 40°C, add 5 parts of polyisocyanate monomer, 2 parts of silane coupling agent, 4 parts of graphene oxide and 40 parts of solvent to the reactor in sequence, heat to 90-110°C, stir under vacuum for 3-6 hours to obtain component A; add component B composed of 96 parts of polyisocyanate curing agent and 4 parts of solvent to component A, stir under vacuum for 1 hour to obtain polyurethane glue.
[0083] The matte surface of the aluminum foil in the aluminum foil laminating CPP semi-finished product and the nylon film 25um are coated and laminated with the above polyurethane glue, and the glue thickness is 3um. The pressure is 0.4MPa, the laminating temperature is 70℃, the oven temperature is 80℃, and the speed is 60m / min to obtain the final product.
[0084] Example 4
[0085] As provided in Example 1, an aluminum-plastic film with high thermal conductivity and high deep drawing performance and a preparation method thereof.
[0086] The aluminum foil with a thickness of 40um is coated on both sides with the passivation liquid to form an acid-resistant film, dried in an oven at a temperature of 240-280°C, and then rolled up for use.
[0087] 60 parts of MPP resin, 30 parts of homopolymer polypropylene resin V30G, 5 parts of lubricating masterbatch C8203ZH, and 5 parts of BN inorganic particles were uniformly mixed to obtain a corona layer resin.
[0088] 90 parts of homopolymer polypropylene resin V30G, 5 parts of lubricating masterbatch C8203ZH, and 5 parts of BN inorganic particles were uniformly mixed to obtain a support layer resin.
[0089] 85 parts of ternary copolymer polypropylene resin TF400, 5 parts of hyperbranched amide resin, 5 parts of slip masterbatch C8203ZH, and 5 parts of BN inorganic particles were uniformly mixed to obtain a heat sealing layer resin.
[0090] The raw materials after the above-mentioned mixed treatment are put into the metering hopper and mixed in proportion, and then enter the corresponding extruder, filter, transmission pipeline, distributor, and T-die head for pressurized melting and plasticization at a temperature of 240°C, and three-layer co-extrusion is extruded through the T-die head at a casting speed of 50m / min, and cooled and crystallized into a film; the thickness of the obtained film is measured, and then the surface of the corona layer is corona treated under the condition of a corona power of 30W / (m2 / min), and the film is pulled and rolled into a film. The film thickness is 50um.
[0091] The passivated aluminum foil bright surface and the CPP film corona layer are hot pressed together at a pressure of 0.4 MPa, a pressing temperature of 170°C, an oven temperature of 220°C, and a speed of 30 m / min. The aluminum foil is pulled and rolled up for use.
[0092] Add 29 parts of polyester polyol and 18 parts of polyether polyol to the reactor, heat to 120°C-130°C, stir under vacuum for 2-3 hours, cool to 40°C, add 5 parts of polyisocyanate monomer, 1 part of silane coupling agent, 5 parts of graphene oxide and 42 parts of solvent to the reactor in sequence, heat to 90-110°C, stir under vacuum for 3-6 hours to obtain component A; add component B composed of 96 parts of polyisocyanate curing agent and 4 parts of solvent to component A, stir under vacuum for 1 hour to obtain polyurethane glue.
[0093] The matte surface of the aluminum foil in the aluminum foil laminating CPP semi-finished product and the nylon film 20um are coated and laminated with the above polyurethane glue, with the glue thickness of 3um, pressure of 0.4MPa, laminating temperature of 70℃, oven temperature of 80℃, speed of 60m / min, to obtain the final product.
[0094] Comparative Example 1
[0095] Provided are an aluminum-plastic film with good thermal conductivity and a preparation method thereof.
[0096] The aluminum foil with a thickness of 40um is coated on both sides with the passivation liquid to form an acid-resistant film, dried in an oven at a temperature of 240-280°C, and then rolled up for use.
[0097] 60 parts of MPP resin, 35 parts of homopolymer polypropylene resin V30G, and 5 parts of lubricating masterbatch C8203ZH were uniformly mixed to obtain a corona layer resin.
[0098] 95 parts of homopolymer polypropylene resin V30G and 5 parts of lubricating masterbatch C8203ZH were uniformly mixed to obtain a support layer resin.
[0099] 90 parts of ternary copolymer polypropylene resin TF400, 5 parts of hyperbranched amide resin and 5 parts of slip masterbatch C8203ZH were uniformly mixed to obtain heat sealing layer resin.
[0100] The raw materials after the above-mentioned mixed treatment are put into the metering hopper and mixed in proportion, and then enter the corresponding extruder, filter, transmission pipeline, distributor, and T-die head for pressurized melting and plasticization at a temperature of 240°C, and are extruded through a T-die head for three-layer co-extrusion at a casting speed of 50m / min, and cooled and crystallized to form a film; the thickness of the obtained film is measured, and then the corona power is 30W / (m 2 The surface of the corona layer was subjected to corona treatment under the condition of 1000 rpm and 2000 rpm, and then the film was drawn and rolled up to form a film with a thickness of 50 μm.
[0101] The passivated aluminum foil bright surface and the CPP film corona layer are hot pressed together at a pressure of 0.4 MPa, a pressing temperature of 170°C, an oven temperature of 220°C, and a speed of 30 m / min. The aluminum foil is then pulled and rolled up for use.
[0102] Add 25 parts of polyester polyol and 15 parts of polyether polyol to the reactor, heat to 120°C-130°C, stir under vacuum for 2-3 hours, cool to 40°C, add 5 parts of polyisocyanate monomer, 5 parts of silane coupling agent and 50 parts of solvent to the reactor in sequence, heat to 90-110°C, stir under vacuum for 3-6 hours to obtain component A; add component B composed of 95 parts of polyisocyanate curing agent and 5 parts of solvent to component A, stir under vacuum for 1 hour to obtain polyurethane glue.
[0103] The matte surface of the aluminum foil in the aluminum foil laminating CPP semi-finished product and the nylon film 20um are coated and laminated with the above polyurethane glue, with the glue thickness of 3um, pressure of 0.4MPa, laminating temperature of 70℃, oven temperature of 80℃, speed of 60m / min, to obtain the final product.
[0104] Comparative Example 2
[0105] Provided are an aluminum-plastic film and a preparation method thereof.
[0106] The aluminum foil with a thickness of 40um is coated on both sides with the passivation liquid to form an acid-resistant film, dried in an oven at a temperature of 240-280°C, and then rolled up for use.
[0107] 60 parts of MPP resin, 35 parts of homopolymer polypropylene resin V30G, and 5 parts of lubricating masterbatch C8203ZH were uniformly mixed to obtain a corona layer resin.
[0108] 95 parts of homopolymer polypropylene resin V30G and 5 parts of lubricating masterbatch C8203ZH were uniformly mixed to obtain a support layer resin.
[0109] 90 parts of ternary copolymer polypropylene resin TF400, 5 parts of hyperbranched amide resin and 5 parts of slip masterbatch C8203ZH were uniformly mixed to obtain heat sealing layer resin.
[0110] The raw materials after the above-mentioned mixed treatment are put into the metering hopper and mixed in proportion, and then enter the corresponding extruder, filter, transmission pipeline, distributor, and T-die head for pressurized melting and plasticization at a temperature of 240°C, and are extruded through a T-die head for three-layer co-extrusion at a casting speed of 50m / min, and cooled and crystallized to form a film; the thickness of the obtained film is measured, and then the corona power is 30W / (m 2 The surface of the corona layer was subjected to corona treatment under the condition of 1000 rpm and 2000 rpm, and then the film was drawn and rolled up to form a film with a thickness of 55 μm.
[0111] The passivated aluminum foil bright surface and the CPP film corona layer are hot pressed together at a pressure of 0.4 MPa, a pressing temperature of 170°C, an oven temperature of 220°C, and a speed of 30 m / min. The aluminum foil is then pulled and rolled up for use.
[0112] Add 30 parts of polyester polyol and 19 parts of polyether polyol to the reactor, heat to 120°C-130°C, stir under vacuum for 2-3 hours, cool to 40°C, add 5 parts of polyisocyanate monomer, 2 parts of silane coupling agent, 4 parts of graphene oxide and 40 parts of solvent to the reactor in sequence, heat to 90-110°C, stir under vacuum for 3-6 hours to obtain component A; add component B composed of 96 parts of polyisocyanate curing agent and 4 parts of solvent to component A, stir under vacuum for 1 hour to obtain polyurethane glue.
[0113] The matte surface of the aluminum foil in the aluminum foil laminating CPP semi-finished product and the nylon film 20um are coated and laminated with the above polyurethane glue, with the glue thickness of 3um, pressure of 0.4MPa, laminating temperature of 70℃, oven temperature of 80℃, speed of 60m / min, to obtain the final product.
[0114] Compared with the technical solution provided by the present invention, the difference in Comparative Example 1 is that no BN inorganic particles are added to the CPP formula, and no graphene oxide is added to the polyurethane glue in the adhesive layer; the difference in Comparative Example 2 is that no BN inorganic particles are added to the CPP formula, and 4 parts of graphene oxide are added to the polyurethane glue in the adhesive layer.
[0115] Specifically, the performance test results of Examples 1-4 and Comparative Examples 1-2 are shown in Table 1 below.
[0116] Table 1
[0117]
[0118]
[0119] Specifically, compared with the example in which no BN inorganic particles were added, the thermal conductivity of Comparative Example 1 was significantly reduced. At the same time, although Comparative Example 2 did not add BN inorganic particles compared to Comparative Example 1, graphene oxide was added to the polyurethane glue, which improved the thermal conductivity and deep punching performance to a certain extent. However, the effect was still far lower than that of Examples 1-4 in which both were added at the same time.
[0120] In summary, the aluminum-plastic film with high thermal conductivity and high punching depth performance and its preparation method, and the lithium-ion battery add high thermal conductivity material boron nitride inorganic particles to the CPP film material to change the crystallization nucleation rate of the CPP film, thereby enhancing the thermal conductivity of the CPP film so that the heat can be quickly conducted to the outside of the battery, and improving the molecular arrangement in the CPP film to an orderly arrangement, combined with the ductility and thermal conductivity of graphene oxide in the adhesive layer, so that the overall thermal conductivity of the aluminum-plastic film is improved and the stress can be evenly dispersed during punching, thereby obtaining excellent punching depth performance.
[0121] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. An aluminum-plastic film with high thermal conductivity and high drawing performance, characterized in that: include: The composite nylon film layer, adhesive layer, aluminum foil layer and CPP film layer are stacked in sequence from outside to inside; The adhesive layer is made of AB two-component polyurethane glue; The A component includes the following components in parts by weight: 20-35 parts of polyester polyol, 15-25 parts of polyether polyol, 5-10 parts of polyisocyanate monomer, 1-5 parts of silane coupling agent, 1-5 parts of graphene oxide and 40-60 parts of solvent; The B component includes the following components in parts by weight: 95-99 parts of polyisocyanate curing agent and 1-5 parts of solvent; The CPP film layers are sequentially composed of a corona layer, a support layer and a heat-sealing layer from the aluminum foil layer outwards, and all of them contain BN inorganic particles.
2. The aluminum-plastic film with high thermal conductivity and high deep drawing performance as claimed in claim 1, characterized in that: The corona layer comprises the following components in parts by mass, and the total parts are 100 parts: 50-60 parts of MPP resin, 30-40 parts of homopolymer polypropylene resin, 1-5 parts of lubricating masterbatch and 1-5 parts of BN inorganic particles.
3. The aluminum-plastic film with high thermal conductivity and high deep drawing performance as claimed in claim 1, characterized in that: The support layer includes the following components in parts by mass, and the total parts are 100 parts: 85-95 parts of homopolymer polypropylene resin, 1-5 parts of lubricating masterbatch and 1-5 parts of BN inorganic particles.
4. The aluminum-plastic film with high thermal conductivity and high deep drawing performance as claimed in claim 1, characterized in that: The heat seal layer comprises the following components in parts by mass, and the total parts are 100 parts: 80-90 parts of ternary copolymer polypropylene resin, 2-8 parts of hyperbranched amide resin, 1-5 parts of lubricating masterbatch and 1-5 parts of BN inorganic particles.
5. The aluminum-plastic film with high thermal conductivity and high deep drawing performance as claimed in claim 1, characterized in that: The mass ratio of the component A to the component B is 100:(20-32).
6. The aluminum-plastic film with high thermal conductivity and high deep drawing performance as claimed in claim 1, characterized in that: The thickness of the nylon membrane layer is in the range of 15-25 μm; The thickness of the adhesive layer is in the range of 3-5 μm; The thickness of the aluminum foil layer ranges from 35 to 55 μm; The thickness of the CPP film layer ranges from 40 to 60 μm; The thickness ratio of the corona layer, the support layer and the heat sealing layer in the CPP film layer is 1:2:
2.
7. The aluminum-plastic film with high thermal conductivity and high deep drawing performance as claimed in claim 1, characterized in that: The particle size of the BN inorganic particles is 100-150 um.
8. The aluminum-plastic film with high thermal conductivity and high deep-drawing performance according to claim 1, characterized in that: The flake thickness of the graphene oxide is 80-120 nm.
9. A method for preparing an aluminum-plastic film with high thermal conductivity and high deep drawing performance as claimed in any one of claims 1 to 8, characterized in that: The steps include: Step S1, mixing various raw materials in proportion and then discharging them in a clean and measured manner; Step S2, program temperature control, setting the temperature of the melt extruder, filter and transmission pipeline to 220-240° C., and the temperature of the distributor and T-die to 240° C., to obtain a filtered melt; Step S3, passing the filtered melt through a T-die and then performing non-mirror casting, and then cooling and crystallizing, and shaping into a film, wherein the casting speed is 40-60 m / min, to obtain a pre-prepared CPP film layer; Step S4, measuring and adjusting the thickness of the pre-prepared CPP film layer, treating the surface with ozone corona to form a corona layer, and then winding the film to obtain a CPP film layer; Step S5, coating both sides of the aluminum foil with an acid-resistant agent to form an acid-resistant film to obtain an aluminum foil layer; Step S6, hot pressing the bright surface of the treated aluminum foil layer and the corona layer of the CPP film, with a pressure of 0.3-0.5 MPa, a pressing temperature of 160-180° C., an oven temperature of 200-220° C., and a speed of 30-40 m / min to obtain a semi-finished aluminum foil layer; Step S7, adding polyester polyol and polyether polyol to a reaction kettle, heating to 120°C-130°C, stirring under vacuum for 2-3 hours, cooling to 40°C, sequentially adding polyisocyanate monomer, silane coupling agent, graphene oxide and solvent to the reaction kettle, heating to 90-110°C, stirring under vacuum for 3-6 hours to obtain component A; adding component B composed of polyisocyanate curing agent and solvent to component A, stirring under vacuum for 1 hour to obtain polyurethane glue; Step S8, coating and bonding the matte surface of the semi-finished aluminum foil layer in step S6 and the nylon film with the polyurethane glue in step S7, with the glue thickness of 3-5um, the pressure of 0.3-0.5MPa, the bonding temperature of 60-70°C, the oven temperature of 70-90°C, and the speed of 60-80m / min to obtain an aluminum-plastic film with high thermal conductivity and high drawing performance.
10. A lithium ion battery, characterized in that: The invention comprises an aluminum-plastic film with high thermal conductivity and high deep drawing performance as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Black adhesive and aluminum-plastic film
CN115305042A
Casting polypropylene composite film for new energy battery aluminum plastic film and preparation method
CN115871302A
Humidity-heat aging resistant polyurethane modified adhesive for lithium battery flexible package and aluminum plastic film
CN116536018A
Heat-conducting high-strength polypropylene composite sheet, fabric of heat-conducting high-strength polypropylene composite sheet, polypropylene composite and preparation method and application of polypropylene composite
CN118849574A
Cited By
Aluminum plastic film, secondary battery and electric device
CN120038988A
Aluminum-plastic film for battery, preparation method of aluminum-plastic film, battery and electric device
CN121546239A